Tingkat Pemahaman dan Dampak Sosial Masyarakat terhadap Syiir Madura Karya Kh. Musfik Al-Karawi - Rosyidi Rosyidi; Thaifur Rahman (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
Syiir is a series of beautiful and refined words composed through linguistic strength and rich imaginative expression. In the context of Islamic da’wah, syiir has long been used as one of the media or approaches by preachers (da’i) to convey religious messages to the community in a persuasive manner that touches emotional aspects. Explicitly, syiir has the ability to stimulate feelings, develop inner awareness, and instill moral and spiritual values, as reflected in various narratives and practices of earlier religious figures. This study, using an integrative–interconnective approach, aims to examine Madurese syiir composed by KH. Musfik Al-Karawi and broadcast through the amateur radio medium YG3AMP, with a focus on the level of community understanding and the resulting social impacts. The research employs a qualitative approach with a case study design. Data were collected through in-depth interviews, field observations, and documentation to obtain a comprehensive understanding of the phenomenon. The findings indicate that the Madurese syiir by KH. Musfik Al-Karawi provides a good level of understanding for the community and generates various positive social impacts. One of the most significant impacts is the transformation of community behavior, reflected in changes from unfavorable attitudes to better ones, and from good behavior to even better conduct in daily life.